Can green credit policy promote low-carbon technology innovation?. (20th July 2022) - Chen, Zhigang; Zhang, Yuqi; Wang, Haisen; Ouyang, Xiao; Xie, Yuxi
Abstract: While the advancing process of achieving the carbon-neutral goal, how green credit policies guide enterprises to green production and low-carbon technology innovation has received much attention Based on the microdata of Chinese enterprises from 2004 to 2019, this paper constructs a difference-in-differences (DID) model according to the Green Credit Guidelines to investigate the impact of green credit policies on enterprises' low-carbon technological innovation and its influence mechanism. The findings include that (1) green credit policy can significantly promote low-carbon technology innovation; (2) green credit policy has a more significant promotion effect on the low-carbon technology innovation of state-owned enterprises and ESG-certified companies; (3) mechanism analysis shows that green credit policies promote enterprises' low-carbon technology innovation by increasing their R&D investment and management efficiency. This study helps policymakers to better understand the impact of green credit policies on low-carbon technology innovation and provides evidence to support the promotion of energy conservation and emission reduction in developing countries.